Uveitic Glaucoma in Recurrent Anterior Uveitic Patient - Santoso, Giovanni Adrian; Wibawaty, Halida; Fairuzia, Amania (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2022)
Introduction: Uveitic glaucoma is a serious disorders that can damage optic nerve and visual field permanently. Management of the disease requires careful diagnosis and adequate control of both IOP and inflammation. A multidisciplinary approach is necessary to achieve a desired outcome. Case Report: A case of a 45-year-old female patient who presented witha chief complaint of red, blurry vision, and dicomfort in the right eye since 1 weeks prior. There was a history of reccurent ante- rior uveiticonthe right eye since 2 years ago. She regularly takes corticosteroid based on the doctor’s advice. Intraocular pressure (IOP) on the right eye was 49 mmHg. This patient underwent trabeculec- tomy + 5-FU without any complications. IOP on the right eye is 16 mmHg postoperative and stable on the next follow up. Visual acuity of the right eye is 0.2F2 because of posterior subcapsular cataract (PSC). Immunomodulator medication was given under internist supervision. Conclusion: Uveitic glaucoma is a complex condition. Appropriate examinations are necessary to prevent further complications. Surgery is needed for patient who doesn’t respond well to anti- glaucoma medical therapy. Observation of postoperative inflammation with topical cortisteroid or oral administration has an important effect in surgical wound recovery. Continuing medication and educa- tion play an important role for long-term visual acuity.